Design Calculations of Multiple Effect Evaporators in Sugar Industry using Visual Basic - Ayuob, Hamza Mohammed; Ali O. Mohammed, Magdi; E. E. Ahmed, Yousif (Gezira Journal of Engineering and Applied Sciences, 2023)
Sugar juice evaporators design is challenging regarding its calculations, complexity, higher energy consumption and much heat exchange equipment used. This paper proposes design calculations software for sugar multiple effect evaporators using Visual Basic. The computer software system was developed via  analyzing the evaporators design process, creating the algorithm, designing the user interface, writing program codes and supplying the components to perform calculations as required. The proposed program was experimentally used to conduct the complex design calculations of multiple effect evaporators. The experimental results for important design variables including  the concentration of the  syrup, the diameter of tubes,  the mass of evaporated water,  the quantity of the heat required and the number of the tubes were found to be: 64.02%; 110.4 kg;, 0.16844 m; , 118175.855 KJ  and 10  respectively. The conducted results were compared to the manually obtained findings and the conducted statistical "T-test" to insure the systems accuracy.